Prednisolone suppresses the immunostimulatory effects of 27-hydroxycholesterol - Kim, Bo-Young (Exp Ther Med, 2020)
In cholesterol-fed rabbits, site-specific targeting of prednisolone nanoparticles results in significantly reduced neo-intimal inflammation with a decreased infiltration of monocytes/macrophages. To understand the molecular mechanisms underlying this, the current study investigated whether prednisolone affects the immune attributes of 27-hydroxycholesterol (27OHChol), the major oxidized cholesterol molecule in circulation and tissue, in human (THP-1) monocyte/macrophage cells. THP-1 cells were exposed to 27OHChol in the presence of prednisolone followed by evaluation of inflammatory molecules at mRNA and protein levels by quantitative PCR, western blotting, ELISA and flow cytometry. The results revealed that prednisolone suppressed the 27OHChol-mediated expression of various macrophage (M)1 markers, including chemokine ligand 2, C-X-C chemokine motif 10, tumor necrosis factor-α and CD80. Treatment also impaired the 27OHCHol-enhanced migration of monocytic cells, downregulated the 27OHChol-induced cell surface expression of CD14 and inhibited the release of soluble CD14 comparable with a weakened lipopolysaccharide response. Furthermore, prednisolone suppressed the 27OHChol-induced expression of matrix metalloproteinase 9 at the transcriptional and protein level, as well as the phosphorylation of the p65 subunit. Prednisolone increased the transcription of CD163 and CD206 genes, and augmented the 27OHChol-induced transcription of CD163 without upregulating the 27OHChol-induced surface protein level of the gene. The results indicated that prednisolone inhibited the polarization of monocytes/macrophages towards the M1 phenotype, which that the immunostimulatory effects of 27OHCHol were being regulated and the immune responses in conditions that were rich in oxygenated cholesterol molecules were being modulated.